X-ray structure of a lectin-bound DNA duplex containing an unnatural phenanthrenyl pair. Issue 26 (22nd February 2016) - Roethlisberger, P.; Istrate, A.; Marcaida Lopez, M. J.; Visini, R.; Stocker, A.; Reymond, J.-L.; Leumann, C. J.
Abstract : DNA duplexes containing unnatural base-pair surrogates are attractive biomolecular nanomaterials with potentially beneficial photophysical or electronic properties. Abstract : DNA duplexes containing unnatural base-pair surrogates are attractive biomolecular nanomaterials with potentially beneficial photophysical or electronic properties. Herein we report the first X-ray structure of a duplex containing a phen-pair in the center of the double helix in a zipper like stacking arrangement.